Evaluation of alternative methods for the disinfection of toothbrushes - Komiyama, Edson Yukio [UNESP]; Back-Brito, Graziella Nuernberg [UNESP]; Balducci, Ivan [UNESP]; Koga-Ito, Cristiane Yumi [UNESP] (FapUNIFESP (SciELO), 2010)
The aim of this study was to evaluate alternative methods for the disinfection of toothbrushes considering that most of the previously proposed methods are expensive and cannot be easily implemented. Two-hundred toothbrushes with standardized dimensions and bristles were included in the study. The toothbrushes were divided into 20 experimental groups (n=10), according to microorganism considered and chemical agent used. The toothbrushes were contaminated in vitro by standardized suspensions of Streptococcus mutans, Streptococcus pyogenes, Staphylococcus aureus or Candida albicans. The following disinfectants were tested: 0.12% chlorhexidine digluconate, 50% white vinegar, a triclosan-containing dentifrice solution, and a perborate-based tablet solution. The disinfection method was immersion in the disinfectant for 10min. After the disinfection procedure, the number of remaining microbial cells was evaluated. The values of cfu/toothbrush of each group of microorganism after disinfection were compared by Kruskal-Wallis ANOVA and Dunn's test for multiple comparisons (5%). The chlorhexidine digluconate solution was the most effective disinfectant. The triclosan-based dentifrice solution promoted a significant reduction of all microorganisms' counts in relation to the control group. As to the disinfection with 50% vinegar, a significant reduction was observed for all the microorganisms, except for C. albicans. The sodium perborate solution was the less effective against the tested microorganisms. Solutions based on triclosan-containing dentifrice may be considered effective, nontoxic, cost-effective, and an easily applicable alternative for the disinfection of toothbrushes. The vinegar solution reduced the presence of S. aureus, S. mutans and S. pyogenes on toothbrushes.
Keywords: Acetic acid; Chlorhexidine; Disinfection; Toothbrushing; Triclosan; acetic acid; boric acid; chlorhexidine; disinfectant agent; drug derivative; toothpaste; triclosan; bacterial count; Candida albicans; chemistry; dental device; disinfection; drug effect; evaluation; human; instrumentation; methodology; microbiology; Staphylococcus aureus; Streptococcus; time; tooth brushing; Acetic Acid; Borates; Colony Count, Microbial; Dental Devices, Home Care; Dental Disinfectants; Dentifrices; Humans; Time Factors